The Effect Of School Rules Towards Students Motivation To Learn English At Mts Al-Urwatul Wutsqo Jombang - Khudriyah Khudriyah (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2024)
The implementation of school rules is important to make students more discipline. This research is aimed to know whether or not the implementation school rules effect students’ motivation to learn English. This research used quantitative approach. Data collected by questionnaire, then it was analyzed using simple linier regression. The result showed that the implementation of school rules at MTs al Urwatul Wutsqo is catagorized at middle, because most of students (46,3%) implemented it in middle category. The student motivation in learning English is catagorized at middle, since many students about 44,44% were motivated in learning English. There is significant effect of school rules towards students motivation in learning English, because the result of hypothesis test showed that the t count is 4.663 > 1.65936. The result of comparing with p-value and its error showed that the significant level of implementation of school rules is known to be 0.000 < 0.05, it means that the regression coefficient for implementation of school rues is significant